The occurrence of L-GALACTONO- 1, 4-LACTONE DEHYDROGENASE (L-GalLDH) in L - ascorbate biosynthesis pathway from photosynthetic eukaryotes - Majed, Sevan O. (Sulaimani Journal for Pure and Applied Sciences, 2016)
L-Galactono-1, 4-lactone dehydrogenase (L-GalLDH) is a key enzyme that catalyzes the last step in the L-ascorbate pathway in biosynthetic eukaryotes. It is widely distributed in the different lineages of photosynthetic eukaryotes. Here, we hypothesized that there is a close evolutionary relationship between L-GalLDHsequences of these eukaryotic lineages. To test this hypothesis, we collected all homologous L-GalLDHsequences of photosynthetic eukaryotes from the NCBI databases. This article reports two results. Firstly, phylogenetic L-GalLDHtree shows that different L-GalLDHs in different species have an evolutionary relationship with each other because these enzymes are descended from a common ancestral gene via gene duplication events at the earliest stage of evolution. The gene duplication events can lead to an emergence of multiple paralogous copy within the species called as In-paralogs and also in different species called as out-paralogs. Moreover, the speciation events can lead to the formation of different L-GalLDHproteins in different species. Because they share from a common ancestral gene, theyhave a close sequence similarity and functional similarity with each other. Secondly, biochemical experimental evidence reveals the presence and absence of the activity of the L-GalLDHenzyme in some lineages of photosynthetic eukaryotes; plants, chlorophyta, phaeophyceae, bryophyta, and pteridophyta. It is worth highlighting a fact that L-GalLDHprotein was only present in the species of a vascular plant (Pisumsativum), chlorophyta (Blindingia minima) and rhodophyta (Porphyra purpurea). This research study attempted to provide a further insight into the L-GalLDHenzymes have been functionally and structurally evolved over distinct lineages of the eukaryotes and over times.
Keywords: Ascorbate; LGalactono1,4lactone dehydrogenas; phylogenetic analysis; gene duplication events